Bone defect filling with a novel rattan-wood based not-sintered hydroxyapatite and beta-tricalcium phosphate material (b.Bone™) after tricortical bone graft harvesting – A consecutive clinical case series of 9 patients. (April 2023) - Alt, Volker; Walter, Nike; Rupp, Markus; Begué, Thierry; Plecko, Michael
Abstract: Harvesting of tricortical bone graft from the iliac crest is an integral part of bone defect reconstruction in orthopaedic surgery. There are several options for filling the iliac crest defect area to avoid hematoma, pain, hernias and cosmetic issues, including different gelatin-based and other alternative biomaterials. Recently, a novel rattan-wood based not-sintered hydroxyapatite and beta-tricalcium phosphate material (b.Bone™, GreenBone ORTHO S.p.A Faenza, Italy) was shown to promote bone healing in an experimental setting. The goal of the current work is to report clinical and radiographical outcomes of a consecutive case series of 9 patients with defect filling at the iliac crest with this novel scaffold biomaterial after tricortical bone graft harvesting with a minimum follow-up of 6 months. All 9 patients (8 male, 1 female) with an average age of 42.7 years (range: 18–76 years) had tricortical bone graft harvesting from the iliac crest for different reconstructive procedures at the extremities and received blocks of the biomaterial with an average size of 26.3 × 16.8 × 10 mm (length, height, width; range: 15 × 15 × 10 to 40 × 20 × 10 mm). Intraoperative handling of the biomaterial was easy and the blocks could be customized to the individual size of the defect with standard surgical instruments and were press-fitted into the defect. All 9 patients showed uneventful wound healing at the iliac crest and 7 patients reported no pain (VAS: 0) and two patients only mild pain (VAS:1 and VAS:3) after an average follow-up of 9.8 months (range: 6–16 months). There was no post-operative hematoma, surgical revision or other implant-related complications at the iliac crest. In all patients, good radiographical integration without dislocation of the implant and good bony integration was observed. The use of this novel biomaterial for iliac crest defect filling was associated with good clinical and radiographical outcomes after an average follow-up of 9.8 months.